EVALUASI KINERJA SISTEM PENGOLAHAN AIR LIMBAH PT. COCA-COLA AMATIL INDONESIA CENTRAL JAVA - Novi Isnasari; Mursid Rahadjo; Nikie Astorina Yunita Dewanti (Jurnal Kesehatan Masyarakat (Undip), 2017)
PT. Coca-Cola Amatil Indonesia Central Java is a company producing soft drinks. Based on the data of liquid waste quality checks in December 2016 showed that phosphate (PO4) level of 2.708 mg / l is still above the standard of 2 mg / l. The purpose of this study is to determine the performance of waste water treatment system PT. Coca-Cola Amatil Indonesia Central Java is viewed from 5 aspects, the operational techniques, institutional, financing, regulation and community participation as well as knowing the influence of lime solution in lowering the liquid phosphate content. The method used in this research is descriptive qualitative and quantitative method with design of quasi-experimental research. The sample used in this research are 4 employees of waste water treatment PT. Coca-Cola Amatil Indonesia and liquid waste PT. Coca-Cola Amatil Indonesia for experimental application of lime for 4 replications and analyzed using Krusskal Wallis and Mann Whitney analysis methods. The results showed effluent of liquid waste produced by PT. Coca-Cola Amatil Indonesia smelly, murky and dirty and the absence of environmental health experts in the processing of liquid waste, most of them are graduates of mechanical engineering graduates. There is influence of lime solution of various variations on the decrease of phosphate content of PT. Coca-Cola Amatil Indonesia (p-value <0,05 ie 0,001), with effective dose 5 ml and efficacy 83,66%.